Functional Materials for Dye-sensitized Solar Cells - S.V. Raksha; V.I. Kondrashin; E.A. Pecherskaya; K.O. Nikolaev (Журнал нано- та електронної фізики)
A review on the analysis of characteristics of dye-sensitized solar cells (DSSC) is provided. DSSC design, materials that are used for the manufacture of functional layers and the characteristics of elements depending on their properties are analyzed. The basic disadvantages DSSC, the factors leading to their appearance, as well as solutions to eliminate or reduce the impact of these factors are revealed.